(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Bangladesh College of Physicians and Surgeons (BCPS), is a constitutional professional academic organization that confers Fellowship (FCPS) and Membership (MCPS) in various specialties in the field of medicine. As a part of evaluation system, BCPS is responsible for continued improvisation of quality assurance process of the Dissertations/Thesis out of a quality research of global standard. On the occasion of golden Jubilee celebration, an effort to document the gradual progression of the system of learning and performing a research and publishing the results by fellows is made through this article. A sub- committee of 6 members assigned by BCPS Journal committee in a group meeting decided to search BCPS library for dissertations and Thesis, dissertations and thesis database of Research and Training Monitoring Department (RTMD), college office for related documents and websites to collect data regarding evolution of thesis/dissertation of BCPS and other institutions at home and abroad. The purpose of this narrative is to describe the evolution of the Dissertation/ Thesis at the BCPS, Dhaka. Until January 2022, a total of 12,575 dissertations and 355 Thesis have been accepted by BCPS. Year wise distribution of outcomes of submitted dissertations from 2010-2022 and thesis submission rate in different specialties are promising. Over the last 50 years, there have been many revisions to the Dissertation submission and assessment guidelines. Funding for research, Mandatory training, training of the trainers, Specialty wise log-book and gradual introduction of regular monitoring of training and research, e-log book, thesis defense all are the few components of evolution of thesis/ dissertation over the years. BCPS council and Research and Training Monitoring Committee (RTMC) strongly believe that there is always room for improvement in the quality assurance process for the research work leading to Thesis submission. This will pave the way for research, publication of articles in renowned journals and collaborative works in future. J Bangladesh Coll Phys Surg 2022; 40: 46-50